2021
DOI: 10.15252/embr.202152835
|View full text |Cite
|
Sign up to set email alerts
|

Resident macrophages restrain pathological adipose tissue remodeling and protect vascular integrity in obese mice

Abstract: Tissue‐resident macrophages in white adipose tissue (WAT) dynamically adapt to the metabolic changes of their microenvironment that are often induced by excess energy intake. Currently, the exact contribution of these macrophages in obesity‐driven WAT remodeling remains controversial. Here, using a transgenic CD169‐DTR mouse strain, we provide new insights into the interplay between CD169+ adipose tissue macrophages (ATMs) and their surrounding WAT microenvironment. Using targeted in vivo ATM ablation followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 74 publications
2
24
0
Order By: Relevance
“…Our results are in agreement with past studies, although the previous analysis was limited only to two CD206 + CD301 + and CD206 -CD301macrophage stromal fractions (12). Interestingly, obesity does not affect the ratio between the three exocrine resident macrophages, nor does it accelerate their turnover rates, as was described in the adipose tissue (27,35). Endocrine F4/80 hi macrophages have been described as longlived embryonic-derived cells that self-renew locally within the islets since birth.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in agreement with past studies, although the previous analysis was limited only to two CD206 + CD301 + and CD206 -CD301macrophage stromal fractions (12). Interestingly, obesity does not affect the ratio between the three exocrine resident macrophages, nor does it accelerate their turnover rates, as was described in the adipose tissue (27,35). Endocrine F4/80 hi macrophages have been described as longlived embryonic-derived cells that self-renew locally within the islets since birth.…”
Section: Discussionsupporting
confidence: 92%
“…2 D ; Chakarov et al, 2019 ; Silva et al, 2019 ). It was recently proposed that the recruitment of eW-ATMs can control vascular integrity during HFD ( Chen et al, 2021 ). Indeed, obesity is characterized by rapid adipocyte expansion and accumulation, thereby drastically affecting AT vascularization, leading to hypoxia and poor vascular system maintenance and growth ( Hodson et al, 2013 ).…”
Section: Dynamism Of the At Niche During Obesitymentioning
confidence: 99%
“…Adipose tissue macrophages (ATMs) are the most abundant immune cell type, which occupy up to 10% of stromal cells under a steady-state and are usually uniformly distributed ( Weisberg et al, 2003 ). ATMs help maintain adipose tissue homeostasis by controlling key signaling pathways involved in adipogenesis, lipogenesis, lipolysis, and lipid uptake ( Kosteli et al, 2010 ; Bilkovski et al, 2011 ; Nguyen et al, 2011 ; Brunner et al, 2020 ; Chen et al, 2021 ). In addition, ATMs play a critical role in the vascular homeostasis of the organ as an adequate blood flow is essential for adipose tissue expansion and metabolic functions.…”
Section: Resident Immune Cells Contribute To Adipose Tissue Homeostas...mentioning
confidence: 99%
“…However, the role of VEGFA in regulating adipose tissue innervation has not been explored to date. In addition, the comparison of adipose tissue obtained from wildtype and ATM-depleted mice revealed that ATMs play a pivotal role in suppressing the expression of pro-inflammatory cytokines ( Chen et al, 2021 ).…”
Section: Resident Immune Cells Contribute To Adipose Tissue Homeostas...mentioning
confidence: 99%